Growth performance and carcass characteristics of lambs raised on varying proportion of roughage and concentrate - KARIM, S A; RAWAT, P S (The Indian Journal of Animal Sciences, 2013)
This study was conducted on native andctossbred weaner lambs to assess their sgowth resqonse and carcass traits under intensive feeding for 90 days on composite rations having 35 (G1),45 (G2), 55 (G3) and 65 (G4) % Zizyphus nummularia leaves in the diet. Initial body weights were similar in the 4 groups, The final weights and ADG were higher (P<0.01) in G1, G2 and G3 compared to G4. Feed conversion efficiency was higher (P<0.01) in G1 (16.2%) and G2 (15.1%) than in G3 (13.4%) and it was lowest in G4 (12.0%). Crossbred had better growth rate. However, their feed conversion efticiency was inferior to native lambs. DMI progressively increased with increase in roughage component, whereas OM digestibility followed reverse trend. Wool yield (6 monthly clip) was similar in treatment groups and it was higher (P<0.01) in crossbred (1.19 kg) compared to their native (0.81 kg) counterpart. The dteSSing percentage (51.9%) and dressing yield inclusive of edible offals (57.3%) and cutability of standard cuts were similar in the treatments and the two genotypes. The carcass fat content of crossbreds was higher than of native lambs and irrespective of treatment regimen the lambs with higher finishing weight had higher carcass fat. The cost offeed inputlkg gain in weight was similar in G 1 (Rs 25.35) and G2 (Rs 25.16) and higher in G3 (Rs 26.17) and G4 (Rs 27.14) whereas it was lower in native (Rs 25.03) than in crossbred (Rs 26.53).